Sotagliflozin, an inhibitor of sodium-glucose cotransporters 1 and 2 (SGLT1/2), as a new therapeutic approach for patients with type 1 diabetes mellitus - Mirella Czapska; Kamila Babkiewicz; Szczepan Pabis; Katarzyna Skórzyńska-Dziduszko (Kazimierz Wielki University, 2018)
Sotagliflozin (SOTA) is a dual inhibitor of SGLT1 and SGLT2 used in adults with type 1 diabetes. The mechanism of action, based on the inhibition of both the SGLT1 and SGLT2 cotransporters, allows simultaneous increase of glucose excretion and slowing down the absorption of glucose in the intestine. Recently, test results have been published showing a beneficial effect of sotagliflozin on type 1 diabetes control [1,2,3]. Sotagliflozin use leads to a significant reduction in glycosylated haemoglobin (HbA1c) [1,2,3] , postprandial glucose reduction [1,2,3], weight loss [1,2,3],  systolic blood pressure reduction  [1,2,3] and reducing the risk of hypoglycaemia during the treatment [1,2,3]. Treatment of type 1 diabetes is based on a model of intensive, functional insulin therapy with the use of human insulin preparations or analogues of this insulin [10]. The therapy is carried out by multiple, subcutaneous injections of insulin doses or in the form of continuous insulin infusion with a personal insulin pump [10]. According to the recommendations of the Polish Diabetes Association (PTD) for patients with type 1 diabetes in terms of glycemic control, the primary goal is to maintain HbA1C  7% (53mmol / mol) and when the goal is not associated with the risk of hypoglycaemia, the target value is  6.5%. The use of proper treatment and sustaining HbA1C at the level recommended by PTD allows to prevent acute and chronic complications of the disease and at the same time allows patients to live actively and, consequently, improves their life quality [10]. According to recently published studies, preparations from SGLT-1 and SGLT-2 inhibitor groups may be helpful in obtaining and sustaining the treatment objective recommended by PTD.